Navigating Organization for Economic Cooperation and Development (OECD) Accession: Institutional Capacity and Governance Reform in Indonesia - Putri, Rara Gusnita; Regiana Revilia; Irsyaad Suharyadi; Fitri Fatharani (International Journal Administration, Business & Organization, 2026)
This study analyzes Indonesia’s accession process to the Organization for Economic Co-operation and Development (OECD) by focusing on institutional capacity and governance transformation. Existing studies on OECD accession largely emphasize economic benefits such as investment inflows and growth acceleration, while limited attention has been given to the institutional readiness and governance capacity of acceding countries, particularly in the Global South. Addressing this gap, this research offers a novel institutional perspective by examining how Indonesia’s bureaucratic capacity, regulatory coherence, and coordination mechanisms shape the effectiveness of accession. This study employs a qualitative case study approach using thematic analysis of official OECD documents, national policy reports, and academic literature. The analytical framework integrates neo-institutionalism with governance capacity indicators to assess reform dynamics. The findings reveal that while OECD accession provides a structured pathway for regulatory harmonization, its success is highly contingent upon institutional capacity, inter-agency coordination, and policy sequencing. Weak administrative capacity risks producing “formal compliance” without effective implementation. This study contributes theoretically by extending neo-institutionalism analysis into accession processes in emerging economies, and practically by proposing an institutional reform roadmap emphasizing coordination mechanisms, monitoring systems, and adaptive governance strategies. The findings suggest that OECD accession should be positioned not merely as an economic strategy but as a long-term institutional transformation agenda.